Discrimination and quantification of sulfathiazole polytypes using low-frequency Raman spectroscopy. Issue 14 (1st March 2018) - Iwata, Kentaro; Karashima, Masatoshi; Ikeda, Yukihiro; Inoue, Motoki; Fukami, Toshiro
Abstract : Low-frequency Raman spectroscopy has advantage to discriminate and quantify polymorphs where common 2D superstructures are piled up with different mode. Abstract : Sulfathiazole forms II, III and IV are polytypes where common monolayers accumulate in different stacking modes. These polytypes are difficult to identify using conventional analytical techniques when they concomitantly crystallize. However, the use of low-frequency Raman spectroscopy enables discrimination of these polytypes and can determine the ratio of forms III and IV, which are the most challenging pair for quantification. A Hydrogen/deuterium exchange study suggests that characteristic patterns below 100 cm −1 predominantly come from differences of superstructure geometries, especially layer stacking, rather than hydrogen-bond geometries. This study demonstrates that low-frequency Raman spectroscopy has advantages for both polytypic discrimination and quantification.